Quality Assurance in Medical Education A Practical Guide - MacCarrick, Geraldine. (Springer London : Imprint: Springer, 2013)
Medical schools across the globe are increasingly being challenged to adopt best practice in training future doctors. Increased accountability as well as rapidly advancing educational and health care developments call for increased sophistication on the part of health educators. Quality Assurance in Medical Education: A Practical Guide is an easy-to-read, practical guide for any medical school preparing for accreditation or institutional review. It contains guidance on the use of internationally accepted standards with a particular focus on what external accrediting bodies look for both before and during their site visit. This book will be particularly helpful to faculties engaged in medical curriculum reform or renewal and those embarking on development of a new curriculum or part thereof, where compliance with internationally accepted standards is paramount. This book will appeal to medical school faculties as well as faculties from other health professions schools and post graduate programs who are preparing for either high stakes accreditation or internal review. It will also appeal to agencies responsible for accrediting medical schools who wish to become more familiar with the international standards.